MEASUREMENT AND ANALYSIS THE IMPACT OF PUBLIC EXPENDITURE ON THE KALDOR'S MAGIC SQUARE VARIABLES IN SAUDI ARABIA USING THE STATISTICAL TECHNIQUE OF AUTO-REGRESSIVE DISTRIBUTED LAG MODEL (ARDL) FOR THE PERIOD 1991–2017 - MOHAMMED HUSSAIN, IBRAHEEM; BAHJAT JAMEEL, SUNDUS (Journal of Duhok University, 2019)
The study aims to measuring and analyzing the effect of public expenditure on the variables of  kaldor's magic square in the Kingdom of Saudi Arabia based on the annual data of public expenditure as an independent variable and the number of dependent variables represented by (unemployment rate, inflation rate, economic growth rate and external balance) for a time series extending from 1991 to 2017, It was found during the study that the spending policy was characterized by high levels over time as a result of the expansion of the role of the government and its activities to effect on the economic and social life, and achieving the goals of the kaldor's magic square is not easy when there was improvement in some axes of the magic square, per contra  there was a deterioration in other axes in the same year, The results revealed that the best period of delay for the variables (growth of public spending, unemployment rate and external balance) was one slowdown while zero for variables (inflation rate and economic growth rate) The results of the unit root test showed that the variables (growth of public expenditure, inflation rate, economic growth rate) were stable at the level, while the variables unemployment rate and external balance were stable at the first difference. After the Bounds test of co-integration, it was found that there is a long-term balance relationship between public spending and inflation, economic growth rate and external balance ; in addition, the short-term effect relationship was positive between public expenditure with (inflation rate, economic growth rate and external balance) and reverse with the unemployment rate; In the long term, the relationship of influence was positive between public expenditure and both the inflation and economic growth rate and inverse with both the unemployment rate and external balance; And through the statistical significance of the value the value (T) shows that public expenditure plays a large role in determining the level of inflation, economic growth rate and external balance. In the short term ; In the long term, public expenditure has played a large role in determining the rate of inflation and the rate of economic growth